Social Determinants of Health Screening at Well Child Visits: A Pilot Program Implemented During the COVID-19 Pandemic - Pyone David MD, MSW; Nadia K. Qureshi MD; Lina Ha MD; Vera Goldberg MD; Erin McCune BS; Jennifer Wojtowicz MPH; Katlyn Sullivan MSc; Garry Sigman MD; Julie C. O'Keefe MD (SAGE Publishing, 2021)
This study demonstrates the challenges of establishing social determinants of health (SDH) screening at well child visits (WCVs) during the COVID-19 pandemic. We conducted a 6-month pre-intervention retrospective chart review (2/2020-8/2020) and 6-month post-intervention prospective chart review (8/2020-2/2021) of an SDH screening and referral protocol at a single suburban academic pediatric clinic. WCVs were screened for food, financial, and transportation needs. With the new protocol, 46% of eligible WCVs (n = 1253/2729) had documented screening results. Self-report of screened visits found 34.6% with financial strain, 32% with worry about food insecurity, 25.1% with food insecurity, 5.3% with medical transportation difficulties, and 6% with daily living transportation difficulties. There was an increase in resources offered during the post-intervention period (OR = 11.5 [7.1-18.6], P  < .001). There was also an increase in resident physician self-reported knowledge in providing referrals ( P  = .04).